2004 emergency response guidebook a guidebook for first responders during the initial phase of a dangerous goods/hazardous materials incident. (U.S. Dept. of Transportation, Research and Special Programs Administration, 2004)
This guidebook was developed for use by firefighters, police, and other emergency services personnel who may be the first to arrive at the scene of a transportation incident involving a hazardous material.
Cover title.
Keywords: United States. -- Department of Transportation. -- Research and Special Programs Administration -- Handbooks, manuals, etc.; United States. -- Department of Transportation. -- Research and Special Programs Administration.; Hazardous substances -- Transportation -- North America -- Safety measures -- Handbooks, manuals, etc.; Hazardous substances -- Toxicology -- North America -- Handbooks, manuals, etc.; Toxicological emergencies -- North America -- Handbooks, manuals, etc.; North America.; elektronické knihy; electronic books